Income and Poverty in Households in Selected European Countries - Ćwiek, Malgorzata Teresa; Ulman, Paweł (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
Incomes of population and poverty are key elements of the EU cohesion policy which aims at reducing disparities between the levels of development of individual regions. The traditionally appropriate study to evaluate the convergence of the Member States is the European Union Statistics on Income and Living Conditions (EU‑SILC). However, this is not the only source of information on income distribution and social inclusion in the European Union. In this article, the basis for calculations are the results of the fourth European Quality of Life Surveys (EQLS), whose purpose is to measure both objective and subjective indicators of the standard of living of citizens and their households. The aim of the paper is to assess the diversity of distributions of household incomes and the level of income poverty due to the selected socio‑demographic characteristics of the respondent or household in selected European countries in two periods: 2007 and 2016. Countries of the Visegrad Group (Poland, the Czech Republic, Slovakia and Hungary) were selected for the analysis, along with the Weimar Triangle (Poland, Germany, and France). Such a selection allowed us to compare the financial situation of households in Western Europe with those in Central and Eastern Europe. Poland becomes a natural link between all these countries. The article uses modelling methods of income distribution, indicators of distance (overlapping) of distributions and aggregate indicators of the scope, depth and severity of poverty. Those ratios were determined on the basis of the use of relative. In order to ensure comparability of incomes of households with different demographic compositions, the analysis used equivalent incomes. As a result of the preliminary analysis, differences were noted regarding the measured position, variation and asymmetry of equivalent incomes in the studied households. The applied gap measurements showed a significant disparity between the distributions of income in Western European countries (Germany, France) and the countries of the Visegrad Group, but the size of that differentation de creased significantly in 2016 relative to 2007. Important differentiation was also noted in terms of income poverty risk within the Visegrad Group: the highest proportion of households at risk of poverty exists in Poland and the lowest in the Czech Republic.